229k views
0 votes
Solve the system of equations by the addition method 5x - 3y = 47x - 2y = 4

User Soredive
by
6.1k points

1 Answer

3 votes

\begin{gathered} \text{Let:} \\ 5x-3y=4\text{ (1)} \\ 7x-2y=4\text{ (2)} \\ \text{Multiply (2) by -3/2:} \\ -(21x)/(2)+3y=-6\text{ (3)} \\ (1)+(3) \\ 5x-(21x)/(2)-3y+3y=4-6 \\ -(11x)/(2)=-2 \\ \text{Solve for x:} \\ -11x=-4 \\ x=-(4)/(-11)=(4)/(11) \\ \text{ Replace x into (1)} \\ 5((4)/(11))-3y=4 \\ (20)/(11)-3y=4 \\ \text{Solving for y:} \\ -3y=4-(20)/(11) \\ -3y=(24)/(11) \\ y=-(1)/(3)(24)/(11)=-(8)/(11) \end{gathered}

User Neil Mackenzie
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.